2022
DOI: 10.3389/fpls.2022.894848
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Transcript Analysis Reveal Potential Roles of Oligopeptide Transporter Genes in Iron Deficiency Induced Cadmium Accumulation in Peanut

Abstract: The oligopeptide transporter (OPT) family is a group of proton-coupled symporters that play diverse roles, including metal homeostasis. However, little is known about this family of peanuts. To reveal the potential roles of AhOPT genes in Fe/Cd interactions, peanut AhOPT genes were genome-widely identified, and the relationships between gene expression and Cd accumulation were detected in two contrasting peanut cultivars (Fenghua 1 and Silihong) under Fe-sufficient or Fe-deficient conditions. A total of 40 AhO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 76 publications
6
7
0
Order By: Relevance
“…Not unexpectedly, we found that Silihong showed a higher capacity for uptake and translocation of Cd from roots to shoots than Fenghua 1 under Fe-deficient conditions ( Figure 8 ). This result is consistent with our previous studies [ 37 , 49 , 51 ]. Similarly, the expression of all AhNRAMP genes except AhNRAMP2.4 was higher in the roots of Silihong than that of Fenghua 1 in the treatments of Fe deficiency with Cd exposure ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Not unexpectedly, we found that Silihong showed a higher capacity for uptake and translocation of Cd from roots to shoots than Fenghua 1 under Fe-deficient conditions ( Figure 8 ). This result is consistent with our previous studies [ 37 , 49 , 51 ]. Similarly, the expression of all AhNRAMP genes except AhNRAMP2.4 was higher in the roots of Silihong than that of Fenghua 1 in the treatments of Fe deficiency with Cd exposure ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, seven AhNRAMP genes showed low expression in most of the 22 peanut tissues under normal conditions ( Figure 6 ). Similar results have been reported in other gene families in peanut [ 49 , 50 , 51 ]. These results support the speculation that reduced expression might be beneficial to retain duplicate genes and their functional redundancy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Arabidopsis, 17 OPT members have been identified and phylogenetically divided into two subfamilies: OPT and YSL [46]. Many OPTs have been shown to be involved in the uptake and translocation of Fe and Cd [47]. OPT1 was also identified in the present study, suggesting that it plays an important role in metal homeostasis.…”
Section: Discussionsupporting
confidence: 56%
“…ahy-miR167-3p targets AhYSL3.2, AhYSL3.4, and AhYSL3.7. all of these miRNAs downregulates their corresponding genes by mRNA cleavage (Wang et al, 2022). Our miRNAs prediction results also revealed their cleaving activity.…”
Section: Discussionsupporting
confidence: 53%